The presence of tartrazine yellow dye in medicines and its health effects: a review of the literature - Quaresma, Andrea Marcela Prestes (2024)
Excipients are substances present in medicines without a therapeutic function, such as the presence of dyes. However, the presence of these dyes has been the subject of scientific studies due to their possible adverse effects on the health of the population, including the appearance of cancer, such as the yellow dye tartrazine. The objective of this study was to evaluate, in literary findings, the possible effects of the tartrazine dye on human health present in medicines. The guiding question was: “Which medicines contain the yellow dye tartrazine and what are the possible health effects caused by this dye”. An Integrative Literature Review (ILR) was carried out, the selection of literature was made through PUBMED, SCIELO, LILACS and repositories of higher education institutions, using the descriptors contained in the DECs: Pharmaceutical Excipients/Pharmaceutical Aids”, “Toxicity/Toxicity” and “Tartrazine/Tartrazine” combined or not with the Boolean operator “And”. The inclusion criteria used were literature available in Portuguese and English, published between 2014 and 2024, with duplicate and paid literature being excluded. Thirteen literatures were chosen that reported that the drugs dipyrone sodium, paracetamol, benzydamine hydrochloride, bropheniramine, phenylephrine, dropropizine and dephenhydramine hydrochloride contain tartrazine yellow as an excipient, in addition to the toxicity, genotoxicity and adverse reactions of tartrazine when ingested gradually or in high quantities. Therefore, it was found that the effects of this dye are alarming, highlighting the need for more detailed studies, so that the competent bodies can subsequently make the necessary decisions. The importance of the pharmacist contributing to information and clarifications about the aforementioned dye is also highlighted.